A screen for genes required for meiosis and spore formation based on whole-genome expression - Rabitsch, Kirsten P.; Schaffner, Gotthold; Moreno Borchart, Alexandra C.; Knop, Michael; Nasmyth, Kim (Current biology, 2001)
Background: Meiosis is the process by which gametes are generated with half the ploidy of somatic cells. This reduction is achieved by three major differences in chromosome behavior during meiosis as compared to mitosis: the production of chiasmata by recombination, the protection of centromere-proximal sister chromatid cohesion, and the monoorientation of sister kinetochores during meiosis I. Mistakes in any of these processes lead to chromosome missegregation. Results: To identify genes involved in meiotic chromosome behavior in Saccharomyces cerevisiae, we deleted 301 open reading frames (ORFs) which are preferentially expressed in meiotic cells according to microarray gene expression data. To facilitate the detection of chromosome missegregation mutants, chromosome V of the parental strain was marked by GFP. Thirty-three ORFs were required for the formation of wild-type asci, eight of which were needed for proper chromosome segregation. One of these (MAM1) is essential for the monoorientation of sister kinetochores during meiosis I. Two genes (MND1 and MND2) are implicated in the recombination process and another two (SMA1 and SMA2) in prospore membrane formation. Conclusions: Reverse genetics using gene expression data is an effective method for identifying new genes involved in specific cellular processes.